(untitled) (Journal of history, 2020)
In this article the author considers the essential problems of the history of Kazakh Khanate at the end of XV – in the beginning of XVI centuries. In the last quarter of the XV century as a result of the successful struggle of Kazakh Khanate for the Syrdarya region Kazakh rulers established their power. In particular the cities along the Syrdarya river is subordinated to the sons of Zhanibek khan. Since that time there are disagreements between the sons of Zhanibek khan and Buryndyk khan. These relations are aggravated at the beginning of the XVI century. Military campaigns of Mohammed Shaibani khan made disagreements between Kazakh rulers in the 1505/6-1510 years. Victory of Kasim khan over Shaibani khan finally set the power of the descendants of Zhanibek all over Kazakh land. Key words: Kazakh Khanate, Burundık Khan, Kasim Khan, The batlle for the near Syr Darya region, Mohammed Shaibani Khan.